Penetration of heavy metals into breast milk and their impact on infant health - research analysis and literature review - Świdniak, Agnieszka; Kopeć, Karolina; Bartoszek, Aleksandra; Adamiuk, Julia; Marut, Agnieszka; Biskup, Marta; Misiuk, Jagoda; Skuba, Adriana; Załuska, Katarzyna; Nykiel, Sylwia (Quality in Sport, 2025)
Introduction and Purpose: Breast milk is considered the best food for infants due to its nutritional and protective properties. However, in the era of increasing environmental pollution, there is a problem of heavy metals penetrating breast milk, which may pose a threat to infants’ health. The aim of the study was to review studies on the presence of heavy metals in mothers’ milk, their sources, mechanisms of penetration, and the impact on infants’ health. Materials and Methods: The work is based on a review of the scientific literature on the content of heavy metals in human milk and their impact on infant development. Publications from peer-reviewed scientific journals, reports from public health institutions and guidelines from organizations such as WHO, EFSA and FDA were used. Data on the levels of lead, mercury, cadmium and arsenic in human milk from different regions of the world were analyzed, taking into account environmental, dietary and lifestyle factors. Results: Research results clearly indicate a significant impact of environmental factors and lifestyle on the content of heavy metals in breast milk, which emphasizes the need for preventive measures and educating women on how to minimize exposure to these substances. Conclusion: The presence of heavy metals in breast milk poses a serious threat to the health of infants. Therefore, it is necessary to implement preventive measures, such as educating mothers about their diet and limiting their exposure to toxic substances. It is also important to conduct biomonitoring and develop effective strategies to reduce environmental pollution. The work emphasizes the importance of further research on the mechanisms of heavy metal transfer to breast milk and their long-term effects on infant health.